Delay in health-care-seeking treatment among tuberculosis patients in Japan: what are the implications for control in the era of universal health coverage? - Yoshikawa, Reina; Kawatsu, Lisa; Uchimura, Kazuhiro; Ohkado, Akihiro (Western Pacific Surveillance and Response, 2020)
Objective: To study the trends in and risk factors for patient delay (the time from the onset of symptoms to the initial doctor visit) in pulmonary tuberculosis (PTB) using three temporal categories - short (2 weeks to < 2 months), medium (2 months to < 6 months) and long (>= 6 months) - and discuss implications for social protection measures. Methods: A descriptive cross-sectional study was conducted by analysing Japanese TB surveillance data from patients with symptomatic PTB registered between 2007 and 2017 (n = 88 351). Results: While the proportion of patients with short delay has decreased significantly (P < 0.001), the proportions of those with medium or long delays have decreased slightly (P = 0.0015 and P < 0.001, respectively). Not having health insurance, receiving public assistance, being a temporary worker, and having a history of homelessness were some of the risks identified for patient delay. Being male and working full-time were two risks specifically associated with long delay (for males, the adjusted odds ratio = 1.17, P < 0.05; for being a full-time worker, the adjusted odds ratio = 1.72, P < 0.05). Discussion: Despite the implementation of universal health coverage decades ago, patient delay remains a challenge in Japan. Our study identified various risk factors, many of which could have been resolved if appropriate social protection measures were in place, indicating shortcomings in universal health coverage in Japan and the need for continued effort to ensure that no one is left behind.